CRITERIA OF ECONOMIC EFFECTIVENESS OF CONTAMINATED TERRITORIES REHABILITATION - Nikolay P. Tikhomirov (Plekhanov Russian University of Economics, 2017)
The article considers four variants of criteria for effectiveness of territories’ ecological rehabilitation illustrated by decontamination of radioactive pollution: with max benefit of decontamination; with min of costs connected with it; with max specific efficiency of costs on decontamination and min costs per unit of prevented damage cost. The authors proved equivalent character of the first and second, third and fourth criteria in pairs. It was shown that the use of first two criteria allows us to get absolute solution of decontamination optimization by the residual dose of radiation and two other criteria can be used only for tasks with restrictions. An example of using the first two criteria for tasks of decontamination optimization was provided.